Choice Of Reading Materials And Reading Achievement Of Junior High Students - Toyong, Paul Junrey A.; Toyong, Marino E. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
Reading is an important skill that can be used to communicate and understand the academic, business and cultural world. Reading can be a tool for learners’ progress and success in different fields of discipline. This study utilized descriptive-correlational design to examine 41 respondents selected as census or total enumeration using purposive sampling. Findings revealed that majority of the respondents used hard copy reading materials for the past 12 months. There were 22 respondents who used books, 2 who used magazines and 1 respondent used newspaper. Most of the class were in frustration level which is 75. 6%. There was one non-reader. Independent readers were four and instructional were five. There was a significant negative relationship (cc= -0.572 and p-value= 0.001) between choice of reading materials and reading achievement. This suggested that the use of soft copies as reading material is correlated to high reading achievement. The implications may serve as basis for intervention, program, and policy formulation. Teachers need to design interactive reading materials using the 21st Century technologies like soft copies reading materials which can be handy and can be access anytime and anywhere using mobile phones. Reading intervention using technology-based materials may be designed to improve reading achievement of the students. Schools may introduce e-library which may introduce various materials that can be accessed and read in soft copy format. This will also be beneficial to distance learning modality.